Pengaruh Pengetahuan Keuangan, Pendapatan, dan Sikap Keuangan terhadap Perilaku Manajemen Keuangan pada UMKM di Daerah Kelapa Tiga Kaliawi Kota Bandar Lampung - Aden Saputra (Bulletin of Community Engagement, 2024)
The researcher aims to find out whether there is a big impact on the way financial managers act. MSME activists in the Kelapa Tiga Kaliawi area of Bandar Lampung City by testing the influence of several variables, including financial knowledge, income, and financial attitudes. This is based on the explanation previously mentioned. The quantitative research method was used by researchers in this study because the data used were in the form of numbers. Small and medium enterprise (SME) restaurant owners in the Kelapa Tiga Kaliawi neighborhood, Bandar Lampung are the population in this study. For this study, a saturated sampling method was used income, and Knowledge, income, and attitudes about money accounted for only 16.9% of the variance in financial behavior, with other variables accounting for the remaining 83.1%. This suggests that financial attitudes do not play an important role in financial management practices. Therefore, this study concludes that the financial management behavior of MSME players in the area is not influenced by financial knowledge, income, or attitude. Kelapa Tiga Kaliawi Area, Bandar Lampung City.